2014
DOI: 10.3733/ca.v068n01p30
|View full text |Cite
|
Sign up to set email alerts
|

Seniors, and their food handlers and caregivers, need food safety and nutrition education

Abstract: Seniors are at greater risk than other adults for foodborne illness, poor nutrition and high rates of nutrition-and lifestyle-related chronic diseases. They also represent a major underserved segment of the UC Cooperative Extension client population. The Make Food Safe for Seniors (MFSFS) initiative assessed food safety and nutrition education needs of fixed-income seniors and food handlers and caregivers serving seniors in 10 California counties. Baseline survey results found unsafe practices by over 50% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…At baseline, all participants first completed a survey, which measures safe food handling knowledge and perceived risk of contracting foodborne illness. The pre-survey included four self-efficacy questions (Table II) adapted from Byrd-Bredbenner et al (2007b); two self-risk assessment questions (Table III) developed by the authors; and 11 food safety knowledge questions adapted from previous work (Blackburn et al, 2014). The post-survey consisted of three program evaluation questions (Table IV) and the same self-risk assessment and food safety knowledge questions in the pre-survey.…”
Section: Methodsmentioning
confidence: 99%
“…At baseline, all participants first completed a survey, which measures safe food handling knowledge and perceived risk of contracting foodborne illness. The pre-survey included four self-efficacy questions (Table II) adapted from Byrd-Bredbenner et al (2007b); two self-risk assessment questions (Table III) developed by the authors; and 11 food safety knowledge questions adapted from previous work (Blackburn et al, 2014). The post-survey consisted of three program evaluation questions (Table IV) and the same self-risk assessment and food safety knowledge questions in the pre-survey.…”
Section: Methodsmentioning
confidence: 99%
“…Caregivers should be skilled in handling food that is safe for the elderly. However, Blackburn et al (2014) found that safe food handling practices are lacking. Most of the caregivers in this study said that safe food preparation is occasionally practiced due to the lack of knowledge about proper food preparation for the elderly.…”
Section: Resultsmentioning
confidence: 99%
“…At the first meeting all participants completed a survey, which measured their safe food handling knowledge, and perceived risk of contracting foodborne illness. The pre-survey included four self-efficacy questions that were adapted from previous work (Byrd-Bredbenner et al, 2007); two self-risk assessment questions developed by the authors; and eleven food safety knowledge questions that were adapted from an educational program delivered in California (Blackburn et al, 2014). At the conclusion of the food safety intervention, participants completed a post-survey which consisted of three program evaluation questions and the same self-risk assessment and food safety knowledge questions in the pre-survey.…”
Section: Methodsmentioning
confidence: 99%